AN ERROR ANALYSIS OF USING SIMPLE PAST TENSE AT THE EIGHTH GRADE STUDENTS OF MTS NEGERI 3 SUKOHARJO IN 2021/2022 ACADEMIC YEAR - Destia TriAstuti; Ch. Evy Tri Widyahening (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2022)
This research were aimed : 1) to find out the types of errors using Simple Past Tense in the Eighth Grade Students, 2) to know the most dominant error made by the students of using Simple Past Tense in the Eighth Grade Students, 3) to identify the causes of error found in using Simple Past Tense in the Eighth Grade Students. This research was conducted on December 2021 until January 2022. The researcher took 25 students in class VIII B of MTs Negeri 3 Sukoharjo. This research was descriptive qualitative research with the type of Error Analysis. To collect the data, the researcher used test, interview and documentation. The data were analyzed by using percentage formula by Corder. The result of the research show that : 1) There were four types of errors found, 138 or 57% error of Omission, 50 or 20% error in Addition, 51 or 21% error in Misformation, and 5 or 2% error in Misordering. The students made total of 244 errors. 2) The most dominant error made by the students of using Simple Past Tense was Omission, because the students made errors by omitting some words and made incomplete sentences. 3) The causes of error found in using Simple Past Tense was the students’ carelessness. It can be concluded that the students had many errors in answering and changing sentences into Simple Past Tense in positive, negative and interrogative forms. The students difficulty in distinguishing between regular and irregular verb. Keywords: Error Analysis, Simple Past Tense, Regular and Irregular verb